PENERAPAN PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE PADA MATERI SEJARAH SENI RUPA UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS X GB 2 SMK NEGERI 2 KARANG BARU ACEH TAMIANG - MUTIA SARI R, Dr. Yahya, M.Pd Dra. Zubaidah. M.Pd (Universitas Negeri Padang, 2013)
The purpose of this research is to out of influenced of the teaching cooperatif learning method type think pair share ti improving motivation and atudent learning outcomes. The research using classroom research method (CAR).The object of this research is students class X GB 2 State SMK 2 Karang Baru Aceh Tamiang. The students divided into 11 groups in pairs. The CAR was done into 2 cyclus in every ciclus used different subject matters of fine art history. The results this study shown that the study results was improved from 68,48 first cyclus, 78,91 at 2nd cyclus. The improving of the student study result not only because of the teaching proses but also by group discussion of the student that implemented Think Pair Share. On the other hand by using of the teaching method above, the student activity and motivation also are improved. The used of the method of Think Pair Share was improved the student understanding because they are got a lot of discussed, drilled, and reading of the teaching materials. Keywords : Method Think Pair Share, Improved Motivation and Learning Outcomes.